The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1093/plphys/kiad099
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA156ab regulates apple plant growth and drought tolerance by targeting transcription factor MsSPL13

Abstract: Drought stress substantially reduces the productivity of apple plants and severely restricts the development of the apple industry. Malus sieversii, a wild apple with excellent drought resistance, is a valuable wild resource for rootstock improvement of cultivated apple (Malus domestica). miRNAs and their targets play essential roles in plant growth and stress responses, but their roles in drought stress responses in apple are unknown. Here, we demonstrate that microRNA156ab is upregulated in M. sieversii in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…In the present study, we successfully knocked down csn-miR156f-2-5p and found that tea plants with csn-miR156f-2-5p knocked down might be more sensitive to drought ( Figure 6 ). This is consistent with previous findings showing that plants with miR156silence are more susceptible to drought stress than the corresponding WT with regard to Arabidopsis and apples [ 48 , 49 ].MicroRNAs function by cleaving the corresponding mRNA or inhibiting translation to regulate the expression of their target genes [ 12 ]. SPLs are genes with crucial roles in plants’ response to abiotic stress and their development, and they are the main target genes of miR156s [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we successfully knocked down csn-miR156f-2-5p and found that tea plants with csn-miR156f-2-5p knocked down might be more sensitive to drought ( Figure 6 ). This is consistent with previous findings showing that plants with miR156silence are more susceptible to drought stress than the corresponding WT with regard to Arabidopsis and apples [ 48 , 49 ].MicroRNAs function by cleaving the corresponding mRNA or inhibiting translation to regulate the expression of their target genes [ 12 ]. SPLs are genes with crucial roles in plants’ response to abiotic stress and their development, and they are the main target genes of miR156s [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
“…We also observed that the expression level of csn-miR156f-2-5p was inhibited by AsODN technology, and the expression level of CsSPL14 was significantly increased ( Figure 8 B). The miR156ab- SPL module has been shown to improve drought resistance by accumulating auxin to maintain growth and by enhancing the activities of antioxidant enzymes in Malus sieversii [ 49 ]. Moreover, the drought tolerance of miR156-overexpressing and SPL13 -silenced plants was significantly improved in alfalfa.…”
Section: Discussionmentioning
confidence: 99%
“…MsSPL13 in Malus sieversii (Feng et al 2023a ), MsSPL8 in Medicago truncatula (Gou J et al 2018 ), MeSPL9 in Manihot esculenta (Li et al 2022b ), and MsSPL9 in M. sativa (Hanly et al 2020 ) negatively regulate drought resistance, while MsSPL13 in M. sativa (Arshad et al 2017 ) and MiSPL13 in Mangifera indica (Zhu et al 2022 ) enhance drought resistance. SbSPL1 is an orthologous gene of M. sieversii MsSPL13 (Feng et al 2023a ) and M. sativa MsSPL13 (Wang et al 2019 ). However, the expression level of SbSPL1 did not change significantly under drought, indicating the species specificity of SPL functions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a transcription factor can act as both a transcriptional activator and a transcriptional repressor. In apple, MaSPL13 repressed MsYUCCA5 and MsPIN7 expression and activated MsGH3.5 expression by binding to GTAC cis -elements in their promoters, thereby affecting aboveground and root development . Thus, although JsLHY is highly sequence conserved with other LHY transcription factors and possesses a conserved MYB-like DNA-binding domain, the partial sequence of its transcriptional regulatory domain is different from that of other homologous proteins (Figure B).…”
Section: Discussionmentioning
confidence: 99%